TOOL ERRORS OF THREE-COORDINATE SENSORS OF VECTOR PHYSICAL QUANTITIES OF THE OPERATING INFORMATION SYSTEMS - S. V. Biryukov; A. V. Tyukin (Вестник СибАДИ)
In this article the question of increase in accuracy of transformation of three-coordinate sensors of vector physical quantities due to their design. Сonstructive errors, characteristic of threecoordinate sensors, are analysed. The analysis was applied to accuracy overall sensitivity of the sensor with three coordinates, and errors caused by the deviation of the axes sensor from orthogonal. It is shown that the error of the overall sensor sensitivity can be reduced to the desired minimum by calibrating the sensor for each coordinate, and the error due to non-orthogonality of the coordinate axes can be significant and reach a few percent (1.75%/deg). To reduce this error must be strict adherence to the orthogonality of the coordinate axes of the sensor.